Behavior of UV-generated carriers and local structure around doped aluminum in anatase titanium dioxide. (January 2019) - Ozawa, Kazuchika; Tanabe, Yusuke; Kodaira, Tetsuya; Sekiya, Takao
Abstract: Al-doped anatase titanium dioxide single crystals and highly Al-doped powders were prepared by chemical vapor transport and by sol-gel process, respectively. Electron paramagnetic resonance (EPR) measurement on the single crystals and powders revealed the characteristic behavior of the UV-induced carriers. The UV-induced EPR sextuplet signals originating from photogenerated holes interacting with Al were observed in both the single crystals and powders. Simulation of the powder pattern of the sextuplet signals observed in EPR measurement indicates that the local structure around the trapped hole in the powder is identical to that of the single crystals. The signal intensity under the UV irradiation and the lifetime of the sextuplets after the UV irradiation decreased with increasing Al content. Rietveld analysis of the X-ray diffraction patterns of the powders revealed that the doped Al substitutes Ti, and that the lattice volume decreases with increasing Al content. The Raman bands of the powders shifted to a higher frequency with increasing Al content. On the basis of these experimental results, the mechanism and the stability of the photogenerated hole are discussed in terms of the dependence of the local structural changes around the doped Al on the Al content. Highlights: The UV-generated hole is trapped at around Al in doped anatase TiO2 . Localization scheme for the hole trapping is independent of the Al content. Localization of the hole in Al-short O bond results in elongation of Al-short O bond. The trapped hole destabilizes with increasing Al content due to chemical pressure.